1999
DOI: 10.1001/archinte.159.8.821
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of the Hands of Hospital Staff During Routine Patient Care

Abstract: Background: Cross-transmission of microorganisms by the hands of health care workers is considered the main route of spread of nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
296
1
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(329 citation statements)
references
References 24 publications
11
296
1
12
Order By: Relevance
“…Sherertz and coworkers documented a fall in catheter related infections from 4.51 to 2.93 infections per 1,000 patients days (p < 0.01) in 18 months after a 1 day infection control training course on venous catheters (9). Several studies have reported high rates of contamination with potentially pathogenic organisms by the hands of health care workers (10,11). Hand disinfection with the use of alcohol based antiseptic hand rub solutions have been shown to be effective in reducing hand contamination (12).…”
Section: Urinary Tract Infection (Uti)mentioning
confidence: 99%
“…Sherertz and coworkers documented a fall in catheter related infections from 4.51 to 2.93 infections per 1,000 patients days (p < 0.01) in 18 months after a 1 day infection control training course on venous catheters (9). Several studies have reported high rates of contamination with potentially pathogenic organisms by the hands of health care workers (10,11). Hand disinfection with the use of alcohol based antiseptic hand rub solutions have been shown to be effective in reducing hand contamination (12).…”
Section: Urinary Tract Infection (Uti)mentioning
confidence: 99%
“…Tangential support to this argument can be gleaned from the literature [11,29,34,43,70,75,84,87,89,92,100,104,125]. The hands of physicians are a known link in the transmission of nosocomial pathogens [70].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
“…The hands of physicians are a known link in the transmission of nosocomial pathogens [70]. In the absence of gloves, there is a considerable increase in bacterial contamination of healthcare workers' hands after patient contact [75,87,100]. Numerous studies have investigated the rates of hand contamination after patient care, and hand contamination may occur even if gloves are worn [11,29,34,43,75,84,87,92,101,125].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
“…8911 In one study, the microbial load on the five fingertips of one hand was as high as 300 CFU following certain high-risk patient care activities; however, the median degree of contamination following the care of any individual patient was only 39 CFU. 11 In contrast, the microbial load introduced to the fingertips of volunteers in the study by Dharan et al was at least 10 7 and rubs were deemed non-efficacious according to the EN 1500 criteria because they were able to reduce microbial counts by "only" approximately 10 4 . 2 Therefore, based on what is known about the degree of contamination that commonly occurs in clinical practice, it appears that the EN 1500 criteria may be excessively stringent.…”
mentioning
confidence: 95%